Efectos de la evaluación de la conformidad del modelo gestión de la calidad NTC-ISO 9001 por ICONTEC (2012)
Conformity assessment is a series of activities to de- monstrate whether a product, a process, a manage- ment system or even a person, meets some specified requirements; framed in the current development of economic globalization, conformity assessment cons- titutes a fundamental element for the deployment of world trade and therefore is governed by international agreements.This article examines with a critical approach, the im- pact conformity assessment can have carried out by the ICONTEC on society, focusing on those organi- zations that voluntarily become certificated. The data analysis is based on a literature review.The findings point to a very positive contribution of certification, to some extent the distribution of the benefits of the global economy is conducted fairly and the observation that the conformity assessment of the quality management system and transnational open markets helps break barriers which brings growth and development